Delimiting species boundaries in Hosta section Capitatae (Asparagaceae) using MIG-seq and morphological analyses: taxonomic revision with new taxa from Korea and Japan - Oh, Ami; Yang, Ji Young; Lee, Won Seok; Shiga, Takashi; Fujii, Seiko; Sakaguchi, Shota; Baasanmunkh, Shukherdorj; Kim, Seung-Chul; Choi, Hyeok Jae (Frontiers in Plant Science, 2026)
IntroductionHosta capitata, which has recently been placed in the monotypic section Capitatae, and H. nakaiana, were originally described in Iya Valley, Japan and Mt. Baegun, Korea, respectively, and have been considered the same from a morphological perspective. However, considering the significant genetic distance between these groups, the identity of H. nakaiana deserves further investigations. Recently, the populations of H. capitata from Kochi, Japan, and Wando Island, Korea have been distinguished from the other groups by their distinctive morphological traits. On the basis of these observations, the present study aimed to provide a complete taxonomic revision of the section Capitatae in Korea and Japan based on extensive morphological observations and multiplexed inter-simple sequence repeats genotyping by sequencing (MIG-seq) analysis.MethodsSamples of the section Capitatae were collected from Japan and Korea. Comprehensive morphological observation of the section Capitatae was performed using both quantitative and qualitative characteristics, and Principal Component Analysis (PCA) was conducted with the quantitative characters. For the molecular analysis of the section Capitatae, MIG-seq library was constructed and SNPs were identified. A phylogenetic tree was inferred using the maximum likelihood (ML) method. The genetic structure of the section Capitatae was determined by performing the STRUCTURE analysis and generating the Principal Coordinate Analysis (PCoA) plot.ResultsThe quantitative characteristics exhibited clear separation between the Kochi lineage and the other groups of the section Capitatae, and the qualitative characteristics showed distinct division between the Wando population and the other groups. The PCA results clearly identified two distinct groups, the Kochi lineage and the others. In the phylogenetic tree, the monophyly of the section Capitatae was strongly supported, and the section Capitatae consisted of three distinct clusters, H. capitata, H. nakaiana and the Kochi lineage. The Kochi lineage was supported as monophyletic (96% BS), and the Wando population was embedded within H. nakaiana cluster. Both the STRUCTURE analysis and the PCoA identified clear genetic differentiation among H. capitata, H. nakaiana and the Kochi lineage.DiscussionOur findings identified three species and two varieties in the section Capitatae. In particular, we described two new taxa, H. pseudonakaiana sp. nov. and H. nakaiana var. wandoensis var. nov., from Japan (Shikoku) and Korea (southern Jeollanam-do), respectively. Our study provides the most comprehensive framework for the classification of the section Capitatae, ultimately advancing the taxonomy of the genus Hosta.